Documentation and Preservation of the Evidences and Reconstruction of A Crime Scene using Augmented Reality, Virtual Reality and Synthetic Reality: Introducing Crime Scene DPR System Bringing the Jury to the Crime Scene - Aditya Saini; Krishan Kumar Sharma; Nikhil Chandra Yadav; Kajol Bhati; Vinny Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
A crime scene, which is the place where a crime has occurred, is suspected of having been committed, or where evidence of a crime has been found, is an essential part of an investigation because it contains all the important details related to the crime. A careful examination of the crime scene can reveal the potential modus operandi of the criminal and establish the Corpus Delicti in court. The first visit to a crime scene is the investigator’s most crucial and often only real opportunity to observe, record, collect, and preserve evidence in its original state. Any subsequent visit holds little to no value, as the scene is usually disturbed, compromised, or altered, either intentionally or unintentionally. Thus, recording a crime became an extremely important step. The typical ways of documenting the crime scene only allow us to view the documents physically; we are unable to provide a visual or allow us to walk to the real crime scene. To help with the investigation, it is crucial to take pictures of the crime scene and any possible evidence. Virtual reality and augmented reality are in high demand right now. Whereas Augmented Reality incorporates a real-world background, Virtual Reality presents an entirely virtualized version of the situation. Virtual reality (VR) is a kind of